2010
DOI: 10.17816/ecogen8256-65
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antigenotoxic effects of juices of plants Chelidonium majus L., Plantago major L. и Tussilago farfara L.

Abstract: The antigenotoxic effects of juices of three medicinal plants, Chelidonium majus L., Plantago major L. and Tussilago farfara L. has been studied in two bacterial tests — SOS chromotest and Rec assay. Antigenotoxic effect was determined against known genotoxic substances — nalidixic acid in SOS chromotest and furacilin in Rec assay. Preparations obtained from the leaves of Ch. majus L. exhibited significant antigenotoxic effect in both the SOS chromotest and the Rec assay. It was shown that dilution of the herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Lee et al [149] reported the (TF)-induced cytotoxic and apoptotic activities of the flower part of T. farfara in human colon cancer cell line (HT-29) by using a methanolic extract. Fatykhova et al [150] showed the genotoxic activity of T. farfara herb juice against known genotoxic compounds like nalidixic acid in SOS chromotest and furacilin in Rec assay. Their findings showed that dilution of the herb juice gave maximum antimutagenic properties in SOS chromotest as compared to furacilin in Rec assay.…”
Section: Tussilago Farfaramentioning
confidence: 99%
“…Lee et al [149] reported the (TF)-induced cytotoxic and apoptotic activities of the flower part of T. farfara in human colon cancer cell line (HT-29) by using a methanolic extract. Fatykhova et al [150] showed the genotoxic activity of T. farfara herb juice against known genotoxic compounds like nalidixic acid in SOS chromotest and furacilin in Rec assay. Their findings showed that dilution of the herb juice gave maximum antimutagenic properties in SOS chromotest as compared to furacilin in Rec assay.…”
Section: Tussilago Farfaramentioning
confidence: 99%
“…farfara in mortal colon cancer cell line( HT-29) by using a methanolic excerpt. Fatykhova et al 114 showed the genotoxic exertion of T. farfara condiment juice against known genotoxic composites like nalidixic acid in SOS chromotest and furacilin in Rec assay. Their findings showed that dilution of the condiment juice gave maximum antimutagenic porperty in SOS chromotest as compared to furacilin in Rec assay.…”
Section: Scutellaria Baicalensismentioning
confidence: 99%
“…В настоящее время изучаются соки из сырья алоэ древовидного, каланхоэ перистого, крапивы двудомной, подорожника большого, мать-и-мачехи обыкновенной, чистотела большого, побегов каллизии душистой и др. [15][16][17][18]. Перспективность разработки лекарственных средств на основе сока из травы манжетки обыкновенной продиктована выявленной у него психомоторной активностью [19].…”
Section: Introductionunclassified